Effect of renoguanylin on hydrogen/bicarbonate ion transport in rat renal tubules - Lessa, L. M. A.; Amorim, José Benedito Oliveira [UNESP]; Fonteles, M. C.; Malnic, G. (Elsevier B.V., 2009)
Renoguanylin (REN) is a recently described member of the guanylin family, which was first isolated from eels and is expressed in intestinal and specially kidney tissues. In the present work we evaluate the effects of REN on the mechanisms of hydrogen transport in rat renal tubules by the stationary microperfusion method. We evaluated the effect of 1 mu M and 10 mu M of renoguanylin (REN) on the reabsorption of bicarbonate in proximal and distal segments and found that there was a significant reduction in bicarbonate reabsorption. In proximal segments, REN promoted a significant effect at both 1 and 10 mu M concentrations. Comparing control and REN concentration of 1 mu M, JHCO(3)(-) . nmol cm(-2) s(-1) -1,76 +/- 0.11(control) x 1,29 +/- 0,08(REN) 10 mu m: P<0.05, was obtained. In distal segments the effect of both concentrations of REN was also effective, being significant e.g. at a concentration of 1 mu M (JHCO(3)(-), nmol cm(-2) s(-1) -0.80 +/- 0.07(control) x 0.60 +/- 0.06(REN) 1 mu m; P<0.05), although at a lower level than in the proximal tubule. Our results suggest that the action of REN on hydrogen transport involves the inhibition of Na(+)/H(+) exchanger and H(+)-ATPase in the luminal membrane of the perfused tubules by a PKG dependent pathway. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Bicarbonate; Guanylins; Microperfusion; Na(+)/H(+); H(+)-ATPase; Kidney